Production Stage and Risk Identification on Asphalt Mixing Plant in Bali - A.A.A Made Cahaya Wardani; I Nyoman Arya Thanaya; Nyoman Yudha Astana; A.A. Gde Agung Yana (International Journal of Applied Business and International Management, 2019)
Cost, quality and time are an important performance indicators in the project success. To achieve these objectives various risks are faced in each project life cycle. One of these risks is supply chain risk, which must be managed properly, doe to the uncertainty in this activity. There are still many companies that do not understand the importance of supply chains, so they often become obstacles in achieving project goals This study aims to identify risk factors in each stage of supply chain activities, in road infrastructure in Bali Province. Data were collected from questionnaire survey, interviews and focus group discussion from 15 units asphalt mixing plant supplier in Bali, who understand supply chain issues, especially in road infrastructure work in the province of Bali. The results of research on risk is firstly AMP production processes identified as a field of manufacturing industry that produces hot asphalt used in infrastructure projects in Bali. This research was conducted at the AMP unit found in Bali. From research, the production process and AMP business are based on Supply, Input, Process, Output and Customer activities. (SIPOC). After the activities contained in the Asphalt production process, it is known that further risks can be identified. Second identity the risk on SIPOC process.